2019
DOI: 10.1080/07370024.2019.1697697
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration on large interactive displays: a systematic review

Abstract: Large Interactive Displays (LIDs), such as tabletops or interactive walls, are promising innovations, which are increasingly used to support colocated collaboration. Yet the current evidence base on the impact of LID use on collaborative processes and outcomes, and associated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…maps, scratch books) only allow for static information and limited interaction. Yet, displaying dynamic information, such as the participants' locations, has proven valuable for enhancing collaboration [5]. A mobile tool allowing for such an interactive shared space would thus be of great benefit for situated collaborative learning in field trips.…”
Section: Situated and Collaborative Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…maps, scratch books) only allow for static information and limited interaction. Yet, displaying dynamic information, such as the participants' locations, has proven valuable for enhancing collaboration [5]. A mobile tool allowing for such an interactive shared space would thus be of great benefit for situated collaborative learning in field trips.…”
Section: Situated and Collaborative Learningmentioning
confidence: 99%
“…Research has shown how digital tools may improve collaborative learning [4]. Having access to a shared interactive space is a key element that facilitates collaborative learning [5]. Such shared interactive spaces are most commonly found in interactive tables: a large touch display, horizontally embedded in a table.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, users can easily lose awareness for what others are doing while working on a different area of the large display [36,43,60,81]. Gutwin & Greenberg [36] state that to maintain workspace awareness, users need to monitor each other's behavior, for instance by showing past interactions of others [37], incorporating visual connections between information [42], using ambient light [65], or embedding animation and off-screen visualization techniques [35,66].…”
Section: C3 Support For Multiple Usersmentioning
confidence: 99%
“…erefore, in order to support collaborative activities, it is suggested that information, skills, roles, or tools are distributed among participants in such a way that they are able to actively operate the relevant objects, determine observation opportunities, and become involved, hands-on. e challenge here is to design collaborative activities that make the most of such affordances for regulating and guiding collaborative work [8,14,20,22,23].…”
Section: Related Workmentioning
confidence: 99%